Integration of the Pentahelix Concept in the Development of Tourism Based Halal Culinary Business - Daryana, Aditiya Pratama; Yudhistira, Prima (Entrepreneurship Faculty, Universitas Garut, 2024)
This study aims to analyze the integration of the Pentahelix model in the development of halal culinary businesses based on tourism destinations in Indonesia. The research objects include three halal tourism villages: Nusa Lhoknga (Aceh), Perlang (Bangka Tengah), and Aeng Tong-Tong (Madura). Employing a qualitative descriptive approach and multiple case studies, data were collected through in-depth interviews, participatory observation, and program documentation. The results reveal that cross-sector collaboration involving government, academics, business, community, and media is crucial to strengthening the halal culinary ecosystem. Four collaboration models were identified, showing the dominant role of local communities and regulatory support in ensuring program sustainability. This research contributes to the conceptual development of the Pentahelix model in value-based creative economies and offers a practical framework for sustainable halal tourism development.